2023
DOI: 10.1093/bmb/ldad017
|View full text |Cite
|
Sign up to set email alerts
|

Mobilization-based engraftment of haematopoietic stem cells: a new perspective for chemotherapy-free gene therapy and transplantation

Abstract: Introduction In haematopoietic stem cell transplantation (HSCT), haematopoietic stem cells (HSCs) from a healthy donor replace the patient’s ones. Ex vivo HSC gene therapy (HSC-GT) is a form of HSCT in which HSCs, usually from an autologous source, are genetically modified before infusion, to generate a progeny of gene-modified cells. In HSCT and HSC-GT, chemotherapy is administered before infusion to free space in the bone marrow (BM) niche, which is required for the engraftment of infused c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 79 publications
0
1
0
Order By: Relevance
“…After transplantation, HSPCs rapidly declined in blood and their subsets were still significantly different from healthy people, the MP-biased differentiation became even more remarkable. Previous studies reported that immunosuppressants, such as sirolimus, block the CXCR4-CXCL12 axis that regulates HSPCs migration and homing 24 . The postoperative HSPCs decline in blood in both AR and NR groups of transplant recipients is possibly caused by immunosuppression therapy.…”
Section: Discussionmentioning
confidence: 99%
“…After transplantation, HSPCs rapidly declined in blood and their subsets were still significantly different from healthy people, the MP-biased differentiation became even more remarkable. Previous studies reported that immunosuppressants, such as sirolimus, block the CXCR4-CXCL12 axis that regulates HSPCs migration and homing 24 . The postoperative HSPCs decline in blood in both AR and NR groups of transplant recipients is possibly caused by immunosuppression therapy.…”
Section: Discussionmentioning
confidence: 99%